2010
DOI: 10.3892/ijo_00000599
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in glioma cells requires cell-to-cell contact with human umbilical cord blood stem cells

Abstract: Abstract. We have previously demonstrated the multipotent nature of human umbilical cord blood stem cells (hUCB). In this study, we have attempted to show the use of hUCB in glioma therapy. We used hUCB enriched in CD44 and CD133 cells for our studies and observed that glioma cells co-cultured with hUCB undergo apoptosis. To prove the role of cell-tocell contact in the induction of apoptotic events, we used a modified 0.22 μm Boyden's chamber where the upper surface was used to culture glioma cells (SNB19 or U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…MSCs are usually isolated from umbilical cord blood or tissues and adipocytes [ 34 - 36 ]. Although much evidence suggests that MSCs can be applied to several diseases, such as cancers [ 1 , 22 , 24 ], cardiac disease [ 8 , 37 ], stroke [ 6 ], and Parkinson and Huntington diseases [ 3 ], the underlying antitumor mechanism of MSCs was not fully understood until now. Thus, in the current study, the antitumor signaling of hUCMSCs was elucidated in PC-3 prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are usually isolated from umbilical cord blood or tissues and adipocytes [ 34 - 36 ]. Although much evidence suggests that MSCs can be applied to several diseases, such as cancers [ 1 , 22 , 24 ], cardiac disease [ 8 , 37 ], stroke [ 6 ], and Parkinson and Huntington diseases [ 3 ], the underlying antitumor mechanism of MSCs was not fully understood until now. Thus, in the current study, the antitumor signaling of hUCMSCs was elucidated in PC-3 prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, hUCMSCs have an immune-suppressive effect or reduced immunogenicity [ 20 ] and express vascular endothelial growth factor (VEGF) and interleukin (IL)-6 [ 18 , 21 ]. Recently, UCB-derived MSCs showed cytotoxicity against glioma [ 22 ] and Kaposi sarcoma [ 23 ], and umbilical cord mesenchymal stem cells suppressed the growth of breast cancer cells [ 24 - 26 ]. Based on previous evidence, in the present study, we investigated the antitumor mechanism of hUCMSCs in PC-3 prostate cancer cells and report that hUCMSCs induce antiproliferative and apoptotic effects in PC-3 cells via activation of JNK and inhibition of the PI3K/AKT pathway in either direct or indirect culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have shown that hUCBSC plays an important role in inducing apoptosis [25] , [26] and reduced migration [27] in glioblastoma cell lines. We focused our present study to determine the regulation of cell cycle progression in the glioma cells when co-cultured with hUCBSC and attempted to determine the potential of hUCBSC to mediate down regulation of cyclin D1, thereby reducing the cell cycle progression by arresting them at G 0 -G 1 phase.…”
Section: Discussionmentioning
confidence: 92%
“…Further, cyclin D1 was co-localized with CD81, confirming the presence of hUCBSC in treated brain samples. In both the cases, during co-localization of hUCBSC with glioma cells, it has been shown that hUCBSC should be in contact with the glioma cells to show their effect [24] , [25] . It is plausible that hUCBSC reduced cyclin D1 expression in glioma cells within their contact and in the surrounding areas ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines, such as vascular endothelial cell growth factors (VEGFs), tumor growth factors (TGFs), epidermal growth factors (EGFs), platelet-derived growth factors (PDGF), monocyte chemoattractant protein-1 (MCP-1), and interleukin-8 (IL-8), which are released from the neoplasm or inflammatory tissues, are all possible candidates for tropism of stem cells. 34 36 Mesenchymal cells augment VEGF-induced angiogenesis in vitro. 37 It is recognized that the factors released from cancer cells promote the movement of endothelial cell progenitors and stromal cell progenitors from the bone marrow toward the tumor 38 , 39 or tissues surrounding the tumor, which enhances the formation of tumor-stroma.…”
Section: Mechanism Of Stem Cell Migration Toward Gliomasmentioning
confidence: 99%